EFFECT OF DIFFERENT LEVEL OF NITROGENOUS FERTILIZER ON LARVAL AND POST LARVAL DEVELOPMENT OF PLUTELLA XYLOSTELLA (LINN.) INFESTING CAULIFLOWER - G. M. BANSODE; M. S. PUROHIT (The Bioscan, 2013)
Nitrogen is one of the most critical chemical elements for plant and herbivores, profoundly influencing development and reproduction. The larval and post larval development of the diamondback moth, Plutella xylostella (Lepidoptera: Pluttelidae), were studied in relation to varying N fertilization levels (160, 80, 40 and 0 kg N/Ha.) in cauliflower (Brassica oleracea var. botrytis L.). The results showed that diamondback moth larvae grew faster gradually when fed with the increasing dose of N fertilization to host plant. However, the upper two levels of N i.e. 80 and 160 kg N/ha did show significant effect on larval development period and it did not influence the adult stage.